US Adults’ Perceptions About the Harms of Nicotine in Electronic Vapor Products on the Adolescent Brain, United States, 2016–2017 - McGruder, Henraya (Prev Chronic Dis, 2020)
We used data from the 2016 and 2017 SummerStyles survey (N = 4,186 and 4,066, respectively) to assess US adults’ perceptions about the harms of nicotine in electronic vapor products (EVP) to the developing adolescent brain. Of respondents in 2016, 68.5% agreed exposure to nicotine in EVP was harmful, and of respondents in 2017, 62.6% agreed (P < .001). This agreement varied by several covariates. Continued efforts are warranted to educate the public about the risks of EVP use among youth, including the harmful effects of nicotine exposure on the developing adolescent brain.